A review of recent methodologies in English language content delivery - Cheng L.K.; Puteh F.; Selamat A.; Bin Mohamed F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Augmented reality; E-learning; Outsourcing; Teaching; Content delivery; Current technology; English language teaching; English languages; Knowledge delivery; Mobile Learning; Research capacities; Teaching strategy; Computational linguistics